The great recession : lessons for Central Bankers - Braude, Jacob editor; Eckstein, Zvi editor; Fischer, Stanley editor; Flug, Karnit editor (Cambridge, Massachusetts : The MIT Press, 2014)
Includes bibliographical references and index